Comparison of Various Predictive Energy Equations for Female University Students With Measured Basal Metabolic Rate: A Pilot Study. Issue 4 (October 2022) - Meseri, Reci; Küçükerdönmez, Özge; Akder, Rana Nagihan
Abstract : The aim of this study was to compare basal metabolic rate (BMR) calculated with various equations and BMR measured using an indirect calorimeter. The study was carried out on second-year university female students (n = 48) with a body mass index of less than 30. Indirect calorimetry with a ventilated hood was accepted as the gold standard and 11 predictive equations were used. Among the equations, Mifflin-St Jeor had the highest correlation ( r = 0.435), but Bernstein (66.7%) and Owen (56.3%) were the most accurate equations. According to Bland-Altman analysis, the lowest bias and the highest explanation were obtained with the Bernstein and Owen equations. More comprehensive studies are needed in different groups to develop new equations with higher accuracy.